2017
DOI: 10.14444/4018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Gait Analysis on a Patient Undergoing Surgical Correction of Kyphosis from Severe Ankylosing Spondylitis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The quantitative analysis of human motion, and especially gait, with cameras, optoelectronic systems, wearable inertial devices, electromyography systems, force plates, and pressure sensors is widely employed for the scientific and clinical investigations of several pathologies. Indeed, the study of gait pattern alterations in patients suffering from spinal disorders is a very active area of research . Traditional gait analysis aims at the measurement of spatiotemporal parameters such as walking velocity, stride and step lengths, cadence, and duration of the stance and swing phases; kinematic parameters such as the angles of rotation of the various joints; kinetic parameters such as forces and moments in the joints, which typically involve the use of force platforms.…”
Section: Applications Of Ai and ML In Spine Researchmentioning
confidence: 99%
“…The quantitative analysis of human motion, and especially gait, with cameras, optoelectronic systems, wearable inertial devices, electromyography systems, force plates, and pressure sensors is widely employed for the scientific and clinical investigations of several pathologies. Indeed, the study of gait pattern alterations in patients suffering from spinal disorders is a very active area of research . Traditional gait analysis aims at the measurement of spatiotemporal parameters such as walking velocity, stride and step lengths, cadence, and duration of the stance and swing phases; kinematic parameters such as the angles of rotation of the various joints; kinetic parameters such as forces and moments in the joints, which typically involve the use of force platforms.…”
Section: Applications Of Ai and ML In Spine Researchmentioning
confidence: 99%
“…Shiba et al [ 25 ] demonstrated significant differences in sagittal alignment between dynamic and static parameters in patients with degenerative lumbar kyphoscoliosis through gait analysis. Similarly, Haddas et al [ 26 ] evaluated kinematics, ground reaction forces, and electromyography results by gait analysis and found significant changes in the spine and lower extremity values in the abnormal spinal sagittal alignment.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Many musculoskeletal and neurological disorders, including CSM, result in altered gait patterns. [9][10][11][12][13][14][15][16][17] These include a slower gait speed, decreased cadence, extended double support duration and stride time, shorter stride and step length, wider step width, and alter muscular activity compared with healthy controls. 13,[18][19][20][21][22] In addition, CSM patients present with more anterior pelvis tilt, larger lumbar lordosis, less cervical lordosis, and less head flexion at the beginning of the gait cycle in comparison to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…CSM is characterized by a wide variety of clinical presentations, which can include neck pain, numbness or weakness in the extremities, hand clumsiness, and classically, gait, and balance disturbances 6–8. Many musculoskeletal and neurological disorders, including CSM, result in altered gait patterns 9–17. These include a slower gait speed, decreased cadence, extended double support duration and stride time, shorter stride and step length, wider step width, and alter muscular activity compared with healthy controls 13,18–22.…”
Section: Introductionmentioning
confidence: 99%